Kajian Pengetahuan Masyarakat Lokal Tentang Pemanfaatan Jamur sebagai Sumber Pangan Masyarakat Di Sekitar Perkebunan Kelapa Sawit Desa Pematang Kancil Kabupaten Merangin - Septian Harmi Lestari; Retni Retni Sulistiyoning Budiarti; Harlis (Jurnal Pro-Life, 2022)
This study aims to determine the knowledge of the community around oil palm plantations in PematangKancil Village, Pamenang District, Meranginakan Regency, types of macroscopic mushrooms and their use. The research location is in Pematang Kancil Village, Pamenang District, Merangin Regency, June-July 2018. The research method is descriptive through in-depth interviews, semi-structured interviews and documentation. Data were analyzed descriptively. The results showed that 58.33% of the people quite understand the existence of fungi in their environment. There are eleven mushrooms that can be used as food sources including: Volvariellavolvacea, Volvariellasp 1, Volvariella sp.2, Pleurotusostreatus (white oyster mushroom), Pleurotusostreatus sp.1, Pleurotusostreatus sp.2, Paxillus volutes (monkey mushroom), Pholia sp. (salary mushroom), Cookeinasulcipes (cup mushroom), Schizophillum commune (nail fungus), Auricularia-auricula-judae (red ear fungus). Indicators of mushrooms that can be used as food sources: inconspicuous color of mushrooms, presence of animals, absence of volva except in Volvariellavolvacea species, not having a ring or cup at the base of the stem. It is recommended to test the chemical content of these mushrooms so that they can be used as a source of medicine and for related devices to socialize these mushrooms to support the community's economy.